Infectious-immune pericarditis: clinical assessment, diagnostics, and differentiated baseline therapy with hydroxychloroquine - O. V. Blagova; G. Yu. Sorokin; V. P. Sedov; E. A. Kogan; N. D. Sarkisova; A. V. Nedostup (Российский кардиологический журнал)
Aim. To study the clinical spectrum of infectious-immune pericarditis, the potential for their invasive and non-invasive diagnosis, as well as long-term treatment with hydroxychloroquine (in comparison with other baseline therapy options).Material and methods. The study included 44 patients with infectious-immune pericarditis (28 women and 16 men aged 49,4±13,3 years). Patients with transudate and specific types of pericarditis were excluded. Levels of C-reactive protein and anticardiac antibodies were determined Multislice computed tomography of the lung (n=23) and heart (n=16), cardiac magnetic resistance tomography (n=9), scintigraphy (n=14), and if necessary — immunoelectrophoresis, DNA testing, Diaskin-test. Pericardio- and thoracentesis were performed in 3/3 patients, thoracoscopic pericardial biopsy — 1, endomyocardial biopsy — 7. The follow-up period was 14,5 [3; 39,5] months.Results. Isolated pericarditis was diagnosed in 10 patients (22,7%), myopericarditis — in 34 (77,3%). In 38 patients, pericarditis was exudative: in 24 (63,2%) with a small effusion (<10 mm), in 10 (26,3%) — with a moderate (11-20 mm), in 4 (10,5%) — with a large (>20 mm). Fibrin was detected in 18,2% of patients. Pericardial effusion was assessed as acute in 4, subacute — in 8, chronic — in 26 patients. The connection between the disease onset and infection was found in 56,8% of patents, and inflammatory blood changes — in 59,1%. In 80%, the punctate was lymphocytic; endomyocardial biopsy confirmed active/ borderline (5/2) lymphocytic myocarditis (virus-positive — in 3 patients). Anticardiac antibody titers were increased in 88,2%. Baseline therapy included NSAIDs (34,1%), colchicine (27,3%), hydroxychloroquine (43,2%), methylprednisolone (56,8%, 16 [16; 21] mg/day), azathioprine (20,5%). The treatment scheme was selected individually. In most cases, combined therapy was carried out. The results of treatment were assessed in 36 patients: an excellent effect was noted in 16 (44,4%) patients, stable effect — in 13 (36,1%), no stable effect — in 7 (19,4%). There were no cases of constrictive pericarditis, acute relapses, cardiac tamponade. Mortality of 6,8% was associated with myocardial injury.Conclusion. Criteria for the diagnosis of infectious-immune pericarditis were proposed. An increase in the titer of anticardiac antibodies was noted in all types of the disease. Prescription of corticosteroids is justified in many cases, including in combination with colchicine, cytostatics, hydroxychloroquine. Hydroxychloroquine monotherapy is effective for subacute/chronic pericarditis with moderate effusion.